ANALISIS KESESUAIAN LKPD DENGAN MODEL PROBLEM BASED LEARNING DI SDN BARENG 1 MALANG - Nita Retno Wahyuningati; Saeful Mizan (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
The purpose of this development research is to Describe the suitability of the Learner Activity Sheet (LKPD) with the Problem Based Learning model. The research method used in this LKPD analysis is descriptive-analytical method. Data collection in this study was carried out by analyzing the LKPD designed by teachers in elementary schools and then analyzed using the PBL model suitability instrument. Based on the results of the analysis that has been carried out using the anggket instrument, it can be seen that the 4th Grade Mathematics LKPD Fraction Material SDN Bareng 1 Malang has achieved 100% suitability so that it can be said that the LKPD is in accordance with the learning model. Grade 5 Mathematics LKPD Semester 1 has not met the suitability criteria of 60%, so that the LKPD is not in accordance with the learning model. LKPD Grade 4 Mathematics Flat Building Perimeter Material has met a percentage of 100%, so it can be seen that the LKPD developed is in accordance with the learning model.